Hepatocellular carcinoma decreases the chance of successful hepatitis C virus therapy with direct-acting antivirals - Prenner, Stacey B. (J Hepatol, 2017)
BACKGROUND & AIMS: The approval of all-oral direct-acting antiviral (DAA) regimens for the treatment of hepatitis C virus (HCV) has led to the expansion of therapy to include patients with cirrhosis who have hepatocellular carcinoma (HCC). Data on the use of DAAs in HCV+ patients with HCC is limited. The aim of this study was to assess the efficacy of all-oral-DAA regimens in HCV+ cirrhotic patients who have or had HCC compared to those without HCC. METHODS: A retrospective cohort study was conducted on all cirrhotic patients who were treated for HCV with DAAs at our institution between January 2014 and November 2015. RESULTS: A total of 421 HCV+ patients with cirrhosis were identified, of whom 33% had active or a history of HCC. Failure to achieve sustained virologic response (SVR) occurred in 21% of patients with HCC compared to 12% of patients without HCC (p = 0.009). Of the 29 patients with HCC who did not achieve SVR, 27 (93%) occurred when an active tumor was present. DAA therapy in the presence of an inactive tumor or after removal of tumor (resection/transplant) resulted in excellent SVR rates, similar to those without HCC (p <0.0001). In multivariable analysis, the primary predictor of DAA treatment failure was the presence of active HCC at the time of HCV treatment initiation (adjusted odds ratio = 8.5, 95% confidence interval = 3.90–18.49). CONCLUSIONS: The presence of active HCC tumor at the initiation of HCV therapy is significantly associated with all-oral DAA treatment failure. HCV treatment after curative therapies for HCC resulted in excellent SVR. LAY SUMMARY: The new medications for hepatitis C have excellent cure rates. However, our study shows that in patients with both liver cancer and hepatitis C, they do not achieve these cure rates. Patients with liver cancer are almost 8 times more likely to fail hepatitis C treatment than patients without liver cancer.